Caregivers’ Sensemaking of Children’s Hereditary Angioedema: A Semiotic Narrative Analysis of the Sense of Grip on the Disease - Freda, Maria Francesca; Savarese, Livia; Dolce, Pasquale; Picione, Raffaele De Luca (Frontiers in Psychology, 2019)
Background and aims: In pediatrics receiving a diagnosis of a chronic condition is a matter that involves caregivers at first. Beyond the basic issues of caring for the physical condition of the ill child, how caregivers face and make sense of the disease orients and co-constructs their children’s sensemaking processes of the disease itself. The aim of this article is to explore the experience of a rare chronic illness, a pediatric case of Hereditary Angioedema (HAE) from the caregivers’ perspective. Hereditary angioedema is characterized by subcutaneous swellings that can involve internal as well as external mucosal tissues and is highly variable and unpredictable in terms of severity, frequency, and where it occurs. A qualitative narrative semiotic analysis of n. 28 maternal narratives on their children’s disease experience. Narratives were collected by an ad hoc interview on three domains of the disease experience: (A) interpretation of disease variability, (B) dialogical processes, and (C) management of the disease. Subsequently, we executed a TwoStep cluster analysis for categorical data to detect cross-sectional profiles of the maternal sensemaking processes of the disease. Results: The coding grid was built analyzing the characteristics of the narrative links that orient the connection between the elements of the experience within each domain: (A) the connection among events, for the domain of disease variability interpretation, (B) the connection between self and other, for the dialogue domain, and (C) the connection among sensemaking and actions, for the disease management domain. Results from the cluster analysis show three narrative profiles: (1) adempitive; (2) reactive; (3) dynamic. Discussion: Profiles will be discussed in light of the general conceptual framework of the Sense of Grip on the Disease (SoGoD) highlighting the importance of those sensemaking processes which, instead of relying on a coherent and closed interpretation of the disease, are characterized by a degree of tolerance for uncertainty and the unknown.